The lima´s society at the beginning of the 20th century explained from a sports match - Alexander Canqui, Glenn (2022)
The matches played by the Alianza Lima and Universitario de Deportes teams in Peruvian soccer are the most attractive for fans of this sport. Beyond football, what makes these meetings so special is the historic rivalry between these clubs. Since their first meeting in 1928 there was already a very marked rivalry, Pulgar Vidal’s work allows us to understand the pre-existing rivalry between both teams through a review of the characteristics of Lima society at the beginning of the s. XX. Reaching the conclusion that, in that first game of 1928, two clubs that represented different social, economic and political sectors within the highly fragmented Lima society faced each other.